Towards a unified approach to research on democratic backsliding. Issue 4 (19th May 2022) - Jee, Haemin; Lueders, Hans; Myrick, Rachel
ABSTRACT: A growing literature examines democratic backsliding, but there is little consensus on when, where, and why it occurs. Reviewing more than 100 recent articles and working papers, this research note argues that inattention to the measurement of backsliding and the underlying concept of democracy drives this disagreement. We propose three remedies. First, we outline several questions that help researchers navigate common measurement challenges. Second, we argue that conceptual confusion around backsliding is driven in large part by inconsistent definitions of democracy. We show how outlining a comprehensive concept of democracy enables researchers to better account for the diversity of instances of democratic backsliding. Our third contribution is drawing attention to a previously overlooked form of backsliding: when governments lose the effective power to govern or voters and elites increasingly disagree about truths and facts. The research note urges scholars to pay closer attention to the conceptualization and measurement of backsliding prior to empirical analysis.